Clasistas, antiimperialistas y revolucionarios Trayectoria política e intelectual del socialismo chileno contemporáneo (1932-1973) - Garrido González, Pablo (Ariadna Ediciones, 2021)
This work reconstructs the political-intellectual trajectory of the Socialist Party of Chile between 1932 and 1973, reviewing its emergence and development in national political life through key moments for the development of party reflection. As stated in its pages, these moments frequently exceeded the limits of party life, being linked to events and processes typical of the global, continental and national political development of the 20th century. It is argued that during the period in question there were a series of debates that accounted for different stages in the organizational, social and intellectual development of contemporary Chilean socialism. These debates were framed in three key concepts that were frequently discussed throughout the trajectory: class, anti-imperialism and revolution. At different times, and with different meanings, the trends defined themselves and their organization as class, anti-imperialist and revolutionary, without there being a consensus on the political and programmatic scope of these definitions.